Mesenchymal Stromal Cells Accelerate Epithelial Tight Junction Assembly via the AMP-Activated Protein Kinase Pathway, Independently of Liver Kinase B1 - P. Rowart; P. Erpicum; J.-M. Krzesinski; M. Sebbagh; F. Jouret (Hindawi Limited, 2017)
Background. Mesenchymal stromal cells (MSC) are fibroblast-like multipotent cells capable of tissue-repair properties. Given the essentiality of tight junctions (TJ) in epithelial integrity, we hypothesized that MSC modulate TJ formation, via the AMP-activated kinase (AMPK) pathway. Liver kinase-β1 (LKB1) and Ca2+-calmodulin-dependent protein kinase kinase (CaMKK) represent the main kinases that activate AMPK. Methods. The in vitro Ca2+ switch from 5 μM to 1.8 mM was performed using epithelial Madin-Darby canine kidney (MDCK) cells cultured alone or cocultured with rat bone marrow-derived MSC or preexposed to MSC-conditioned medium. TJ assembly was measured by assessing ZO-1 relocation to cell-cell contacts. Experiments were conducted using MDCK stably expressing short-hairpin-RNA (shRNA) against LKB1 or luciferase (LUC, as controls). Compound STO-609 (50 μM) was used as CaMKK inhibitor. Results. Following Ca2+ switch, ZO-1 relocation and phosphorylation/activation of AMPK were significantly higher in MDCK/MSC compared to MDCK. No difference in AMPK phosphorylation was observed between LKB1-shRNA and Luc-shRNA MDCK following Ca2+ switch. Conversely, incubation with STO-609 prior to Ca2+ switch prevented AMPK phosphorylation and ZO-1 relocation. MSC-conditioned medium slightly but significantly increased AMPK activation and accelerated TJ-associated distribution of ZO-1 post Ca2+ switch in comparison to regular medium. Conclusions. MSC modulate the assembly of epithelial TJ, via the CaMKK/AMPK pathway independently of LKB1.